The dynamics of innovative behavior in sports professionals: An ecological dynamics approach to the serial mediation of motivation and cognitive flexibility in the influence of perceived social support - Hasan Buğra Ekinci; Ahmet Yavuz Mallı (PLoS ONE, 2026)
This study aims to explain how perceived social support is associated with innovative behavior in sports professionals. The psychological processes explaining this relationship are not sufficiently explained in the literature; in particular, the roles played by intrinsic motivation and cognitive flexibility in this process need to be investigated in more detail. In this context, the sequential mediating roles of these two variables were tested within the framework of the Ecological Dynamics Approach, and a comprehensive model that could contribute to the development of innovative practices was proposed. This cross-sectional study was conducted using data collected from 243 sports professionals working in the province in Eastern Turkey. To examine the predictive role of perceived social support on innovative behavior, a series of mediation models were tested using the PROCESS macro. In this model, intrinsic motivation and cognitive flexibility were positioned as sequential mediators. The analysis revealed that perceived social support did not have a statistically significant direct link with innovative behavior; instead, this relationship was mediated entirely through intrinsic motivation and cognitive flexibility. Specifically, the sequential mediation pathway was found to be significant, in which perceived social support is positively associated with intrinsic motivation and then cognitive flexibility, which in turn relates to higher levels of innovative behavior. The findings support the Ecological Dynamics Approach, which posits that innovative behavior is a dynamic product of individual-environment interaction. Social support functions not only as a motivational factor but also as a contextual affordance that supports cognitive flexibility. This study provides a theoretical and practical framework for explaining the psychological mechanisms that support innovation in sports.